Zero and uniqueness sets for Fock spaces. Issue 2 (25th June 2023) - Aadi, D.; Omari, Y.
Abstract: We characterize zero sets for which every subset remains a zero set too in the Fock space $\mathcal {F}^p$, $1≤ p<∞ $ . We are also interested in the study of a stability problem for some examples of uniqueness set with zero excess in Fock spaces.